Factor Effecting Firm Value: The Role Of CSR in Plantation Firm Indonesia - Situmorang, Frenky (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine and analyze the effect of firm size, profitability, sales growth, and good corporate governance on firm value with social responsibility as a moderating variable in plantation companies listed on the stock exchange. The data collection method used is secondary data with the population in this study being plantation companies listed on the stock exchange. The study sample was 14 companies from 2013 - 2017 with a total of 70 observations (5 years). The data analysis model is used to test the hypothesis of multiple linear regression models and Moderated Regression Analysis (MRA). The results showed that firm size had a negative effect on firm value, profitability had a positive effect on firm value, sales growth and good corporate governance were not significant to firm value. Corporate social responsibility is able to moderate the firm size and good corporate governance towards firm value. Corporate social responsibility is not able to moderate profitability and sales growth towards firm value.